Analisis Sektor Ekonomi Unggulan di Kabupaten Lebak Periode Tahun 2016-2020 - Anita Widiastuti (FEB Universitas Sultan Ageng Tirtayasa, 2022)
Lebak Regency is one of the regencies located in Banten Province which has a strategic position with great potential and natural resources. The advantages possessed by Lebak Regency must be utilized by development in various sectors which become strengths to be able to increase economic growth in Lebak Regency. This study aims to determine the leading economic sector in Lebak Regency for the 2016-2020 period. This study uses secondary data in the form of Gross Regional Domestic Product data on the basis of constant prices by business sector in Lebak Regency and Banten Province in 2016-2020. The analytical method used in this research is Location Quotient (LQ) and Shift-Share Analysis (SSA). The results of the study indicate that there are 6 (six) leading sectors based on the results of LQ analysis and based on SSA there are 5 (five) economic sectors that have fast growth and have high competitiveness.